Gender Equality in the Perspective of Amina Wadud and Its Relevance to Gender Politics in Lampung Province - Restiyani; Nadirsah Hawari; Gesit Yudha (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
Gender equality in Muslim societies remains marked by a persistent gap between normative Islamic ideals and socio-political realities, particularly in women’s political participation and leadership. This study examines Amina Wadud’s feminist hermeneutics and its relevance to gender politics in Lampung Province, Indonesia. Employing a qualitative socio-legal approach, the research integrates textual analysis of Wadud’s major works with a critical review of literature on gender and political representation in Indonesia. Focusing on principles of contextual Qur’anic interpretation, spiritual equality, and anti-hierarchical theology grounded in tawḥīd and justice (al-‘adl), the study finds that political gender inequality stems not from Islamic doctrine but from patriarchal interpretations, masculinized institutions, and entrenched cultural norms. Despite increased visibility of women in Lampung’s political arena, participation remains largely symbolic and constrained by conservative religious readings. This study contributes to Islamic feminist scholarship and fiqh siyāsah by demonstrating that feminist hermeneutics provides a normative and epistemological foundation for advancing substantive gender equality through cultural, institutional, and theological transformation.